The best school year ever ebook - Robinson, Barbara (The Herdmans, 2011)
Lionsgate is releasing a live action movie version of The Best Christmas Pageant Ever on November 8, 2024, directed by Dallas Jenkins of The Chosen and featuring actors Judy Greer, Lauren Graham, Elizabeth Tabish, and Pete Holmes, coming to a theater near you! The Herdmans are back so buckle up for a wild ride involving a missing gerbil, a crazy cat, and a tattooed baby that will have readers of all ages laughing! This hilarious novel stars the Herdmans, the worst kids in the world, who made their first appearance in author Barbara Robinson's classic The Best Christmas Pageant Ever. In The Best School Year Ever, Imogene, Claude, Ralph, Leroy, Ollie, and Gladys Herdman haven't changed a bit. They still set things on fire and knock the other kids black and blue. One day the teachers ask all the students to think of compliments for their classmates, and Beth Bradley picks Imogene Herdman's name. At first, Beth can't think of anything good, but soon she begins to see Imogene in a new light. Maybe behind all of the outrageous pranks, there is something good about the Herdmans?